Training Tomorrow's Doctors to Safeguard the Patients of Today: Using Medical Student Simulation Training to Explore Barriers to Recognition of Elder Abuse. Issue 1 (19th January 2016) - Fisher, James M.; Rudd, Matthew P.; Walker, Richard W.; Stewart, Jane
Abstract : In recognition of the fact that elder abuse is a global problem that doctors underrecognize and underreport, a simulation training session for undergraduate medical students was developed. The primary objective of this qualitative study was to examine barriers to and drivers of medical students making a diagnosis of elder abuse in simulated practice, with the goal of refining teaching methods and informing future teaching sessions for other clinical teachers. Third‐year medical students (Newcastle University, United Kingdom) undertook a simulation scenario with a high‐fidelity mannequin representing an elder abuse victim. After the simulation scenario, students underwent a semistructured debriefing. A tripartite approach to data collection was employed that included audio recordings of the simulation, data sheets capturing students' thoughts during the scenario, and postscenario debriefing. A different researcher analyzed each data set in isolation before discussions were held to triangulate findings from the data sets. Forty‐six students undertook the scenario; none declined to participate. A number of barriers to students diagnosing elder abuse were identified. Students held a low index of suspicion for elder abuse and were overly optimistic regarding the etiology of the individual's injuries. Students lacked the confidence to raise concerns about possible elder abuse, believing that certainty was required before doing so. There was widespread confusion about nomenclature. These findings provide clinical teachers with important topic areas to address in future teaching sessions. Simulation, as a method to teach about elder abuse in a reproducible and immersive fashion, is recommended to clinical teachers.